Mecanismos jurídicos de acceso a la tierra: situación actual y perspectivas de futuro - Zumaquero-Gil, Laura (Universidad de Valladolid, 2025)
Access to land is one of the biggest problems faced by farmers who wish to enter this sector. Hence the importance of analysing this issue in order to adopt appropriate measures to facilitate access. Among all these measures, the existence of regulations that adequately govern the various mechanisms for accessing and holding land is a key element in providing solutions to this issue. In this paper addresses the issue of access to land from a regulatory point of view, analysing the regulation of the different legal instruments in Spanish law that allow access to land, whether under a regime of ownership or individual or shared use. It analyses the classic mechanisms for access to land, but also new models that are being implemented very successfully in some Autonomous Communities. Furthermore, it presents and analyses the generational renewal policies that Spain is implementing in this area, as well as proposing some measures that we believe could facilitate access to land for young farmers.
Keywords: Agricultores - Derecho - Legislación; Tierras de cultivo - Derecho; Generational renewal; New models; Regime of ownership; Legal mechanisms; Access to land